In Silico Stage-Matching of Human, Marmoset, Mouse, and Pig Embryos to Enhance Organ Development Through Interspecies Chimerism - Shetty, Anala; Lim, Seunghyun; Strell, Phoebe; Steer, Clifford J.; Rivera-Mulia, Juan Carlos; Low, Walter C. (Cell transplantation, 2023)
Currently, there is a significant shortage of transplantable organs for patients in need. Interspecies chimerism and blastocyst complementation are alternatives for generating transplantable human organs in host animals such as pigs to meet this shortage. While successful interspecies chimerism and organ generation have been observed between evolutionarily close species such as rat and mouse, barriers still exist for more distant species pairs such as human–mouse, marmoset–mouse, human–pig, and others. One of the proposed barriers to chimerism is the difference in developmental stages between the donor cells and the host embryo at the time the cells are introduced into the host embryo. Hence, there is a logical effort to stage-match the donor cells with the host embryos for enhancing interspecies chimerism. In this study, we used an in silico approach to simultaneously stage-match the early developing embryos of four species, including human, marmoset, mouse, and pig based on transcriptome similarities. We used an unsupervised clustering algorithm to simultaneously stage-match all four species as well as Spearman’s correlation analyses to stage-match pairs of donor–host species. From our stage-matching analyses, we found that the four stages that best matched with each other are the human blastocyst (E6/E7), the gastrulating mouse embryo (E6–E6.75), the marmoset late inner cell mass, and the pig late blastocyst. We further demonstrated that human pluripotent stem cells best matched with the mouse post-implantation stages. We also performed ontology analysis of the genes upregulated and commonly expressed between donor–host species pairs at their best matched stages. The stage-matching results predicted by this study will inform in vivo and in vitro interspecies chimerism and blastocyst complementation studies and can be used to match donor cells with host embryos between multiple species pairs to enhance chimerism for organogenesis.